Second world war in American film - Šafránek, David (Univerzita Pardubice, 2009)
This bachelor thesis deals with contemporary American war film set in the Second World War. It presents historical and cultural context of war film evolution. Then it deals with established procedures in war films in general. On the sample of three films it then presents various approaches to the topic and at the same time points out common elements.
Druhá světová válka v americkém filmu
Keywords: Druhá světová válka; americké filmy; válečné filmy; Spielberg; Bay; Eastwood; Second World War; American films; war films; Spielberg; Bay; Eastwood